Effect of cycling inactivity and cycling speed on hazard mitigation - Tan, Song Keat (2019)
In recent years, cycling has become increasingly popular in Singapore, but accident rates involving cyclists have also increased as well. Cyclists’ perception and reaction towards hazards are critical to the avoidance of accidents, and can be affected by cyclists’ demographic factors, cycling speed and the hazard conditions. This study aims to determine the effect of cycling inactivity and cycling speed on hazard mitigation, in terms of cyclists’ response time and response behaviour towards the hazard. A simulated cycling environment was used in this study, focusing on a covert hazard in which a pedestrian walked onto the cyclist’s path from a concealed opening to the side. The proposed independent variable of cycling inactivity was defined based on a threshold inactivity period of 3 months, while cycling speed was considered at the point where the cyclist first fixated his/her eye gaze on the hazard pedestrian. The proposed dependent variable of response time was considered in terms of total response time or Response Latency (RL), as well as sub-components of Lag Time (LT), Time to Fixation (TF), and Perception-Intellection-Emotion-Volition (PIEV) time. Response behaviour was classified into swerving, braking and both swerving and braking.